2019
DOI: 10.15275/rusomj.2019.0108
|View full text |Cite
|
Sign up to set email alerts
|

Association of erythrocyte sedimentation rate and C-reactive protein and clinical findings with HLA-DQ8 allele in Rheumatoid Arthritis patients

Abstract: Background-Rheumatoid arthritis (RA) is an inflammatory, autoimmune disease induced by certain auto-antigens. HLA-DRB1*0401 allele has a significant relationship with RA incident. Additionally, DQβ1*0301, *302(DQ8), *303, and *304 can increase RA risk especially in DQA1*0301 and *302 coincident. Recent studies suggest that distribution of this allele is different in various populations Material and Methods-70 patients and 70 healthy controls were analyzed for human leukocyte antigen (HLA) allele by specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Dysregulated immune stimulation and chronic inflammation are the most noteworthy studied risk for lymphomagenesis in ARD patients. Information on the disease characteristics along with the general reviewing of the systems in ARD patients can unveil the development of some worrisome signs that raise the suspicion of LPD development, e.g., high ESR values, erosive joint diseases, lymph node enlargement, organomegaly, night sweating, fever, and weight loss may alarm the development of malignancy [15][16][17]. It is suggested that pathogenesis of ARD that resulted from chronic B cell activation and inflammation are risk determinants of malignant transformation of B cells and lymphoma development.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated immune stimulation and chronic inflammation are the most noteworthy studied risk for lymphomagenesis in ARD patients. Information on the disease characteristics along with the general reviewing of the systems in ARD patients can unveil the development of some worrisome signs that raise the suspicion of LPD development, e.g., high ESR values, erosive joint diseases, lymph node enlargement, organomegaly, night sweating, fever, and weight loss may alarm the development of malignancy [15][16][17]. It is suggested that pathogenesis of ARD that resulted from chronic B cell activation and inflammation are risk determinants of malignant transformation of B cells and lymphoma development.…”
Section: Introductionmentioning
confidence: 99%